Mesenchymal stem cells-derived exosomes attenuate mouse non-heart-beating liver transplantation through Mir-17-5p-regulated Kupffer cell pyroptosis - Yang Tian; Ming Jin; Nanwei Ye; Zhenzhen Gao; Yuancong Jiang; Sheng Yan (Stem Cell Research & Therapy)
Abstract Background Liver transplantation is the most effective treatment for end-stage liver disease. However, the shortage of donor livers has become a significant obstacle to the advancement of liver transplantation. Mesenchymal stem cells-derived exosomes (MSCs-Exo) have been extensively investigated in liver diseases. However, the underlying mechanisms of how they can protect organ donation after cardiac death (DCD) livers remain unclear. Methods In this study, an arterialized mouse non-heart-beating (NHB) liver transplantation model was used to investigate the effect of MSCs-Exo on NHB liver transplantation. The survival rates, histology, pro-inflammatory cytokine and chemokine expression, and underlying mechanisms were investigated. Results The infusion of MSCs-Exo reduced the injury to DCD liver graft tissue. In vitro and in vivo experiments demonstrated that MSCs-Exo could inhibit hydrogen peroxide-induced pyroptosis of Kupffer cells. We found that miR-17-5p was significantly abundant in MSCs-Exo, targeting and regulating the TXNIP expression. This action inhibited NLRP3-mediated pyroptosis of Kupffer cells through the classical Caspase1-dependent pathway, alleviating DCD liver graft injury. Conclusion Our study elucidated a protective role for MSCs-Exo in a NHB liver transplantation model. This mechanism provides a theoretical basis and new strategies for the clinical application of MSCs-Exo to improve liver graft quality and alleviate the organ shortage in liver transplantation.